Description of the Role of the Young Generation in the Preservation of Mauluik Culture in Padang Pariaman District - Ilham Riadi; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
This research is based on the phenomenon of still maintaining the implementation of religious culture, one of which is called the Mauluik Korong Toboh Tangah tradition, Padang Pariaman Regency. This is thought to be due to the role of the younger generation in order to preserve Mauluik culture in aspects of developing, maintaining, and adjusting so that the mauluik culture still survives. This type of research is a quantitative descriptive. The population in this study were young people aged 16-30 years and domiciled in Korong Toboh Tangah, Padang Pariaman Regency with a total of 40 people. The sampling technique used was simple random sampling, which took 75% of the population to 30 people. Data collection techniques using a questionnaire. While the data collection tool is a list of statements. Data analysis techniques using the percentage formula. The results showed that the role of the younger generation in the preservation of Mauluik culture in Korong Toboh Tangah, Padang Pariaman Regency, aspects of developing are good, maintaining good, and adjusting are also good. This is proven by the majority of youth giving answers always. Based on the results of the study it is recommended to youth to be able to increase motivation to be more active in instilling cultural values that exist.Keywords: Young Generation, Preservation, Mauluik